2022
DOI: 10.3389/fendo.2022.856954
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Biological Functions of Dipeptidyl Peptidase-4 in Bone Metabolism

Abstract: Dipeptidyl peptidase-4 (DPP4) is a ubiquitously occurring protease involved in various physiological and pathological processes ranging from glucose homeostasis, immunoregulation, inflammation to tumorigenesis. Recently, the benefits of DPP4 inhibitors as novel hypoglycemic agents on bone metabolism have attracted extensive attraction in many studies, indicating that DPP4 inhibitors may regulate bone homeostasis. The effects of DPP4 on bone metabolism are still unclear. This paper thoroughly reviews the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 178 publications
(190 reference statements)
0
9
0
1
Order By: Relevance
“…In term of DPP-4i, [82][83][84][85][86][87][88][89] almost all are balanced for fracture reduction, including vildagliptin (RR, 1.17; 95% CI, 0.23-6.16), sitagliptin (RR, 1.29; 95% CI, 0.27-6.47), omarigliptin (RR, 1.33; 95% CI, 0.21-8.24), saxagliptin (RR, 2.04; 95% CI, 0.38-12.09), linagliptin (RR, 0.9; 95% CI, 0.18-4.66), and alogliptin (RR, 0.76; 95% CI, 0.12-4.87); however, trelagliptin seemed to significantly increase the risk of fracture with RR of 3.51 (95% CI, 1.58-13.70). 82 In terms of sulfonylureas, the data also failed to support the benefits of fracture reduction, although the trend seemed to favor the use of this type of medication for fracture reduction during DM control, including glimepiride (RR, 0.45; 95% CI, 0.31-4.25), glipizide (RR, 0.67; 95% CI, 0.12-3.74), gliclazide (RR, 0.75; 95% CI, 0.05-9.46), and glibenclamide (RR, 0.98; 95% CI, 0.22-4.25).…”
Section: Antidiabetic Agents and Bonementioning
confidence: 99%
See 2 more Smart Citations
“…In term of DPP-4i, [82][83][84][85][86][87][88][89] almost all are balanced for fracture reduction, including vildagliptin (RR, 1.17; 95% CI, 0.23-6.16), sitagliptin (RR, 1.29; 95% CI, 0.27-6.47), omarigliptin (RR, 1.33; 95% CI, 0.21-8.24), saxagliptin (RR, 2.04; 95% CI, 0.38-12.09), linagliptin (RR, 0.9; 95% CI, 0.18-4.66), and alogliptin (RR, 0.76; 95% CI, 0.12-4.87); however, trelagliptin seemed to significantly increase the risk of fracture with RR of 3.51 (95% CI, 1.58-13.70). 82 In terms of sulfonylureas, the data also failed to support the benefits of fracture reduction, although the trend seemed to favor the use of this type of medication for fracture reduction during DM control, including glimepiride (RR, 0.45; 95% CI, 0.31-4.25), glipizide (RR, 0.67; 95% CI, 0.12-3.74), gliclazide (RR, 0.75; 95% CI, 0.05-9.46), and glibenclamide (RR, 0.98; 95% CI, 0.22-4.25).…”
Section: Antidiabetic Agents and Bonementioning
confidence: 99%
“…82,86 Although in Taiwan, DPP-4 inhibitors (DPP-4i) effect on the bone health in T2DM patients seemed to be supported by largescale population-based study as shown by Dr. Chang's group, 56 and additionally, DPP-4 has been extensively reviewed to provide the possible benefits on bone and subcutaneous tissue (extracelluar matrix), which are key factors of bone health. 89,90 Similar to many large-scale population-based studies, 31,56,63,[83][84][85][86][91][92][93][94][95][96][97][98] many biases, which cannot be totally excluded, may decrease the reliability and reproducibility of the data analysis. Additionally, DPP-4i may increase the risk of cholecystitis in randomized controlled trials, especially with longer treatment duration, 99 although the population-based cohort study did not support the current use of DPP-4i was associated with an increased risk of bile duct and gallbladder disease compared with current use of at least 2 oral ADA (adjusted HR, 0.99; 95% CI, 0.75-1.32).…”
Section: Antidiabetic Agents and Bonementioning
confidence: 99%
See 1 more Smart Citation
“…7 Animal studies raised concerns regarding glucagon-like peptide-1 (GLP-1) receptor agonists and dipeptidyl peptidase-4 (DPP-4) inhibitors due to their potential interaction with osteoclast activity, despite not being supported by human studies. 8,9 The effects of GLP-1 and glucagon receptor dual agonists or triple agonists of the glucose-dependent insulinotropic polypeptide (GIP), GLP-1, and glucagon receptors on bone health are also worth attention because the concentration of glucagon was positively correlated with bone turnover markers in type 2 diabetes. 10 Given the diversity of underlying mechanisms between different anti-diabetic drugs and fractures, the time-to-event duration could vary across drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the CANVAS trial suggested that sodium‐glucose cotransporter‐2 (SGLT2) inhibitors may elevate the risk of fracture by increasing dehydration‐related falls 6 but subsequent trials did not confirm the finding 7 . Animal studies raised concerns regarding glucagon‐like peptide‐1 (GLP‐1) receptor agonists and dipeptidyl peptidase‐4 (DPP‐4) inhibitors due to their potential interaction with osteoclast activity, despite not being supported by human studies 8,9 . The effects of GLP‐1 and glucagon receptor dual agonists or triple agonists of the glucose‐dependent insulinotropic polypeptide (GIP), GLP‐1, and glucagon receptors on bone health are also worth attention because the concentration of glucagon was positively correlated with bone turnover markers in type 2 diabetes 10 .…”
Section: Introductionmentioning
confidence: 99%